2017
DOI: 10.5430/jha.v6n5p12
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization patterns of antidepressants in Federal Neuro-Psychiatric Hospital Lagos, Nigeria

Abstract: Backgroud: The paucity of information on prescribing patterns and use of antidepressants in accordance with practice guidelines necessitated this study in Nigeria. Objective: To assess the prescribing patterns of antidepressants, average cost of prescriptions and the index of rational drug prescribing (IRDP) in a Nigerian tertiary care hospital. Methods: A retrospective study which involved the assessment of 683 prescriptions and case records of patients who received antidepressants from 1 st January 2013 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…• The most common medicines prescribed by psychiatrists for patients with BD are typical antipsychotics either alone or in combination with mood stabilizers [174]. Tricyclic antidepressants were the most prescribed antidepressant in the majority of studies conducted in tertiary hospitals in patients with depressive symptoms, with lower costs if clinicians follow published STGs [175,176].…”
Section: Nigeriamentioning
confidence: 99%
“…• The most common medicines prescribed by psychiatrists for patients with BD are typical antipsychotics either alone or in combination with mood stabilizers [174]. Tricyclic antidepressants were the most prescribed antidepressant in the majority of studies conducted in tertiary hospitals in patients with depressive symptoms, with lower costs if clinicians follow published STGs [175,176].…”
Section: Nigeriamentioning
confidence: 99%
“…We identi ed fteen studies through this review, and the majority of the patients were in the economically productive age group of 40-50 years [25][26][27][28][29][30][31][32][34][35][36][37][38][39] , whereas in the result of a study on antidepressant use in Italy, the mean age of the patients who received antidepressant prescriptions was more than 50 years 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Our review showed that the majority of the patients receiving antidepressants for the treatment of their depression were females 27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] . This could be due to hormones that are associated with the regulation of the menstruation cycle and pregnancy affecting mood in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations